THE EXPANSION OF THE UNIVERSITY SPACE IN KYIV (the history of the first facilities of the university of st. Volodymyr) - Taras Samchuk (Місто: історія, культура, суспільство, 2017)
The history of the first facilities of st. Vladimir University and its situation in the city in 1830-40s were not in the centre of special research before. That’s why the first period of the university existing can’t be fully described. For this reason, the aim of the study is to highlight the history of the first leased buildings of st. Vladimir University in the context of the formation of university space.